Analisa Business Strategy Planning Menggunakan Analisis SWOT dan Analytic Network Process (ANP) di PT. Heksa Artha Sakti - Seiman mas jaya daeli; Achmad Misbach (Jurnal Industri dan Teknologi Samawa, 2024)
PT Heksa Artha Sakti is a subsidiary of Heksa Group, which is responsible for distributing all products from Heksa Group. Distributor offices of PT. Heksa artha sakti are located almost throughout Indonesia, In the midst of tough competition in Indonesia, PT. Heksa artha sakti has competitors who have a very large market share, so that sales are unstable for six months which is an indication of the need to evaluate and improve the company's marketing management itself. The purpose of this study is to adjust the criteria that have been ranked and weighed and to assist decision makers with the company's vision and mission. This study uses SWOT analysis and Analytic Network Process (ANP). The selection of company strategies considered at PT Heksa Artha Sakti is the company's management capability (0.121335), the company has adequate facilities (0.088277), high-quality products (0.111173), and uses less modern technology in production (0.081609). The four sub-criteria are Because based on the results of the ANP priority analysis, respondents gave the highest priority to these sub-criteria. The results of the ANP priority analysis show that the selection of the right strategy for the company is priority 1, establishing relationships with new customers, expanding the marketing area by using sales techniques and using existing technology and purchasing raw materials at medium cost with the same quality, which has the highest weight based on the limiting value, namely 0.067936, this proves that it is important to make improvements to management, especially in the marketing sector, to achieve the company's goals.